Impacts of Improved Switchgrass and Big Bluestem Selections on Yield, Morphological Characteristics, and Biomass Quality - Erik Delaquis; Roger Samson; Philippe Seguin; Arif Mustafa; Huguette Martel (Advances in Agriculture)
Switchgrass (Panicum virgatum L.) and big bluestem (Andropogon gerardii V.) are promising warm-season grasses for biomass production. Understanding the morphological and quality-related traits of these grasses can guide breeders in developing strategies to improve yield and quality for bioindustrial applications. Elite selections were made in Southern Quebec from four promising varieties of switchgrass and one of big bluestem. Biomass yield, morphological characteristics, and selected quality traits were evaluated at two sites in 2011 and 2012. Significant variation was detected for all measured characteristics, with differences varying by site and year. In some cases the selection process modified characteristics including increasing height and reducing tiller mortality. Switchgrasses reached a similar tiller equilibrium density in both years of 690 m−2 and 379 m−2 at a productive and marginal site, respectively. Differences in yield were pronounced at the marginal site, with some advanced selections having a higher yield than their parent varieties. Switchgrass yields were generally greater than those of big bluestem. A delayed spring harvest date greatly reduced yield but reduced moisture content and slightly increased cellulose concentration. Big bluestem had a higher cellulose content than switchgrass, likely due to greater stem content.